Perubahan Iklim Dan Dampaknya Pada Indonesia - Darwin Hartono (STIE AMKOP, 2023)
Climate change is real and several sectors in Indonesia are experiencing its impacts so that the government and society should be aware of what is happening. The impacts of changes in rainfall patterns and extreme climate events occur on land and water resources, plants, increasing air temperatures, and rising sea levels and tidal waves. The strategy for dealing with climate change is by using water and climate management technology, rain harvesting technology, ditch dam technology, and irrigation technology and the most important part is building public awareness of climate change. Key Words: Climate Change, Agriculture Sector, Public Awareness, Indonesia